2021
DOI: 10.15541/jim20200522
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-assisted Synthesis and Co, Al Co-modification of Ni-rich LiNi0.8Mn0.2O2 Materials for Li-ion Battery Electrode

Abstract: Due to high specific capacity and cost performance, high-nickel cathode materials have received much attention. However, its further application is hindered by poor stability and safety performance during cycling. In this work, Ni-rich LiNi0.8Mn0.2O2 materials were prepared through microwave-assisted co-precipitation followed by high-temperature solid-phase method, which can be further modified by doping different proportions of Co and Al.The as-prepared materials are characterized and tested with different me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The columnar illustration in Figure a lists the first Coulombic efficiencies of different electrode materials; the NM@Sn-2 electrode achieves the highest with a value of 87.97%, which is better than that of the previously reported cathode. , This suggests that a proper amount of Li 2 SnO 3 modification can improve the electrochemical reversibility of the material and inhibit side reactions, thereby increasing its reversible capacity. The cyclic performances of the corresponding electrodes at different conditions are illustrated in Figure b (25 °C) and Figure c (55 °C), with a higher current density (1 C ).…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations
“…The columnar illustration in Figure a lists the first Coulombic efficiencies of different electrode materials; the NM@Sn-2 electrode achieves the highest with a value of 87.97%, which is better than that of the previously reported cathode. , This suggests that a proper amount of Li 2 SnO 3 modification can improve the electrochemical reversibility of the material and inhibit side reactions, thereby increasing its reversible capacity. The cyclic performances of the corresponding electrodes at different conditions are illustrated in Figure b (25 °C) and Figure c (55 °C), with a higher current density (1 C ).…”
Section: Resultsmentioning
confidence: 86%
“…The Ni 0.8 Mn 0.2 (OH) 2 precursors were prepared by the microwave-assisted co-precipitation method. , In the conventional synthesis route, stoichiometric NiSO 4 ·6H 2 O and MnSO 4 ·H 2 O are weighed at a mole rate of 8:2 and dissolved in distilled water to form a 500 mL 2.0 mol L –1 mixed metal salt solution. 500 mL of an alkaline solution consists of 4 mol L –1 NaOH solution and 4 mol L –1 NH 3 ·H 2 O solution.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Amongst various candidates, LiNi x Mn 1−x O 2 with a layered structure is a type of prospective positive electrode material because of its high discharging capacity, cost-effectiveness, good thermal stability and large Li + density. 4 Many lithium nickel manganate cathode materials, such as LiNi 0.7 Mn 0.3 O 2 , 5,6 LiNi 0.8 Mn 0.2 O 2 7,8 and LiNi 0.9 Mn 0.1 O 2 , 9,10 have been extensively explored. Numerous studies have shown that the energy density of batteries increases with increasing nickel concentration in LiNi x Mn 1−x O 2 .…”
mentioning
confidence: 99%